The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1086296x16653842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Paired Literacy Program on Emerging Bilingual Children’s Biliteracy Outcomes in Third Grade

Abstract: This longitudinal study examined whether the implementation of a SpanishEnglish paired literacy approach provides an academic advantage to emerging bilingual students over a sequential literacy approach. The study employed a quasiexperimental design. It compared the biliteracy outcomes of third-grade emerging bilingual learners participating in paired literacy instruction from Grades K-3 (n = 167) to those of students from the same schools who received sequential literacy instruction in K-2 and started to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Finally, in 8% of the studies, students were exposed to simultaneous literacy instruction. Simultaneous literacy instruction is grounded in the idea that children can acquire literacy in two languages simultaneously (Escamilla, 2006) and that dual-language instruction should start when students enter school (Soltero-González et al, 2016). It is important to note that the articles in this group all highlighted Literacy Squared ® , “a comprehensive biliteracy framework made up of four main components: paired literacy instruction, professional development, assessment of biliteracy skills, and research” (Soltero-González et al, 2016, p. 85).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 8% of the studies, students were exposed to simultaneous literacy instruction. Simultaneous literacy instruction is grounded in the idea that children can acquire literacy in two languages simultaneously (Escamilla, 2006) and that dual-language instruction should start when students enter school (Soltero-González et al, 2016). It is important to note that the articles in this group all highlighted Literacy Squared ® , “a comprehensive biliteracy framework made up of four main components: paired literacy instruction, professional development, assessment of biliteracy skills, and research” (Soltero-González et al, 2016, p. 85).…”
Section: Resultsmentioning
confidence: 99%
“…This framework is both research-based and research tested. Our research indicates that adherence to these guidelines in Spanish-English bilingual education settings results in significant language and literacy achievement for Spanish-English bilingual learners (Hopewell & Escamilla, 2013;Soltero-González et al, 2012, 2016Sparrow et al, 2014). And, while we have not analyzed data from monolingual educational settings, we have worked with teachers and administrators in such settings and have sufficient anecdotal evidence to convince us that there is value in using these principles in those settings as well.…”
Section: Valuing Two Languages: a Holistic Biliteracy Frameworkmentioning
confidence: 95%
“…Literature has widely reported that one's background can either positively or negatively impact how one rates candidates. Raters' backgrounds include rating experience (Huang et al, 2018;Ahmadi Shirazi, 2019;Şahan and Razı, 2020), training experience (Duijm et al, 2017;Bijani, 2018Bijani, , 2019, teaching experience (Kang and Veitch, 2017;Eckstein and Univer, 2018;Kang et al, 2019), raters' first language (Hijikata-Someya et al, 2015;Marefat and Heydari, 2016;Ahmadi Shirazi, 2019;Kang et al, 2019), familiarity about candidates (Huang et al, 2016;Tanriverdi-Koksal and Ortactepe, 2017;Wikse Barrow et al, 2019), personal traits, gender (Bijani and Khabiri, 2017;Protivínský and Münich, 2018), academic achievement (He et al, 2013;Soltero-González et al, 2016), age (Soltero-González et al, 2016;Isbell, 2017), and cultural background (Stassenko et al, 2014). In terms of raters' experiences, three types of experience are widely examined, which are rating experience, training experience, and teaching experience.…”
Section: Raters' Experiencementioning
confidence: 99%